Paul Stoller, The Power of the Between, An Anthropological Odyssey, University of Chicago Press, Chicago, London 2009., 201. str. - Potkonjak, Sanja (2011)
Rad je prikaz knjige Paula Stollera - The Power of the Between. An Anthropological Odyssey.
Projekt MZOS
HRV